Exploring the Influential Factors on Readers' Continuance Intentions of E-Book APPs: Personalization, Usefulness, Playfulness, and Satisfaction - Liu, Hehai; Shao, Mingming; Liu, Xiaohong; Zhao, Li (Frontiers in Psychology, 2021)
This study analyzed and summarized the literature related to the electronic book (e-book) applications (APPs) and undergraduates’ continuous intention, combined with the characteristics of the e-book APPs, introduced relevant theories and variables, and established the factors that influence undergraduates’ continuous intention of using e-book APPs. On this basis, the paper analyzed the relationship of various influencing factors and their influence on the continuous intention. A model composed of 5 hypotheses was constructed to test the factors influencing undergraduates’ continuous intention in e-book APPs. The results indicated that of all research variables, satisfaction is the most important factors that affects the continuous intention; Perceived usefulness and perceived playfulness have an indirect effect on continuous intention through satisfaction; Personalization has direct effects on perceived usefulness and perceived playfulness, so it also have an indirect effect on continuous intention.